Aramid fiber coated diaphragm, preparation method thereof and electrochemical device
By applying an aramid coating with inconsistent pore size structure on the power battery separator, the battery safety and cycling performance problems caused by transition metal ion migration are solved, and the fast charging effect with high porosity is achieved.
Patent Information
- Application Number
- CN202411823717.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
During the charging and discharging process of power batteries, the migration of transition metal ions causes the separator to be pierced, affecting the safety and cycling performance of the battery. At the same time, fast charging requires high porosity diaphragms that cannot effectively block the migration of metal ions.
An aramid-coated separator is used, which includes a base film and an aramid coating containing aramid and inorganic filler coated on one side of the base film. The cross-sectional porosity of the aramid coating is 28.5-46%, and shows inconsistent pore sizes in the thickness direction. The porosity of the 1/2 thickness region of the surface is less than the porosity of the 1/2 thickness region of the inner 1/2 thickness region.
Effectively block and adsorb the dissolved transition metal ions, improve the liquid absorption and ionic conductivity of the separator, achieve fast charging under high-rate conditions, while maintaining good heat shrinkage performance, safety and circulation performance of the battery.
Smart Images

Figure CN119651053A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery diaphragms, and in particular to an aramid coated diaphragm and a preparation method thereof and an electrochemical device. Background Art
[0002] Compared with traditional internal combustion engine vehicles, electric vehicles have two major problems: weak endurance and long charging time. The use of high-nickel ternary (Ni>80%) and other positive electrode materials and silicon-carbon negative electrode, metal lithium negative electrode and other negative electrode materials can achieve a significant increase in the energy density of power batteries. In addition, when the power battery charging rate is increased to 4.6-6C, it can meet the charging of 20 miles (about 32.19 kilometers) per minute or be fully charged to 80% in 10 minutes, which is comparable to the time it takes to fill up the gas tank of an internal combustion engine vehicle (usually 5-10 minutes).
[0003] However, there are many problems in the implementation of the above approach. On the one hand, the electrolyte byproduct HF during the charge and discharge process will cause the transition metal in the positive electrode material to dissolve and then migrate to the negative electrode surface. After the voltage reaches the reduction potential of the above transition metal elements in the battery formation stage, a metal element is formed at the negative electrode. When it accumulates to a certain extent, the edges and corners of the metal element can easily pierce the diaphragm, which leads to battery self-discharge. In addition, under the catalytic action of reduced metal manganese, the SEI on the negative electrode surface accelerates decomposition and destruction, and the irreversible consumption of lithium ions increases, which ultimately affects the battery safety and cycle performance. On the other hand, fast charging requires the diaphragm to have a high porosity to ensure efficient conduction of lithium ions in the battery, but high porosity means that it cannot effectively prevent metal ions from migrating to the negative electrode. Therefore, the above requirements of power batteries put forward higher requirements on the heat resistance and microstructure of the diaphragm (pore size distribution, porosity, etc.). Summary of the invention
[0004] One of the purposes of the present invention is to provide an aramid coated diaphragm, which, on the one hand, is beneficial for blocking and adsorbing dissolved transition metal ions, and has a high porosity, which can ensure the diaphragm's high liquid absorption and retention capacity, is beneficial for improving ionic conductivity and thus achieving fast charging under high rate conditions.
[0005] A second object of the present invention is to provide a method for preparing the aramid coated diaphragm.
[0006] A third object of the present invention is to provide an electrochemical device comprising the aramid coated diaphragm.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] A first aspect of the present invention provides an aramid coated diaphragm, the aramid coated diaphragm comprising:
[0009] Basement membrane, and
[0010] An aramid coating containing aramid and an inorganic filler coated on at least one side of the base film, wherein the inorganic filler is filled in a fiber network structure formed by the aramid;
[0011] The cross-sectional porosity of the aramid coating is 28.5-46%, preferably 34.1-44.5%, and the aramid coating shows inconsistent pore sizes in the thickness direction, wherein the ratio of the cross-sectional porosity in the 1 / 2 thickness area on the surface of the aramid coating to the cross-sectional porosity in the 1 / 2 thickness area inside the aramid coating is <1.
[0012] Preferably, the cross-sectional porosity of the 1 / 2 thickness region on the surface of the aramid coating is 25.4-43.6%, preferably 36.0-41.0%.
[0013] Preferably, the cross-sectional porosity of the 1 / 2 thickness region inside the aramid coating is 31.6-45.4%, preferably 39.0-44.0%.
[0014] like Figure 1 As shown in, the aramid coated diaphragm of the present invention comprises a base film 1 and an aramid coating 2 formed on at least one surface of the base film 1, wherein the aramid coating 2 comprises aramid 3 and an inorganic filler 4, and the pore size formed by the aramid 3 and the inorganic filler 4 varies in the thickness direction. The ratio of the cross-sectional porosity (i.e., the porosity of the cross-sectional pores) of the 1 / 2 thickness region 21 located on the surface of the aramid coating (away from the base film side) to the cross-sectional porosity (i.e., the porosity of the cross-sectional pores) of the 1 / 2 thickness region 22 located inside the aramid coating (close to the base film side) is <1.
[0015] "Inconsistent (uneven) pore size in the thickness direction, where the ratio of the porosity of the cross-sectional pores located in the 1 / 2 thickness area on the surface of the aramid coating to the porosity of the cross-sectional pores located in the inner 1 / 2 thickness area of the aramid coating is <1" should be understood as the cross-sectional porosity of the 1 / 2 thickness area on the surface of the aramid coating is less than the cross-sectional porosity of the inner 1 / 2 thickness area, including all ways in which the aramid coating can form the above pore size structure, for example, the cross-sectional overall pore size (cross-sectional porosity) of the aramid coating increases linearly from the surface to the base membrane; the cross-sectional overall pore size (cross-sectional porosity) of the aramid coating increases nonlinearly from the surface to the base membrane; the cross-sectional overall pore size (cross-sectional porosity) of the aramid coating increases discontinuously from the surface to the base membrane; and so on.
[0016] The cross-sectional porosity (or cross-sectional pore porosity) of the present invention refers to the percentage of the pore area on the cross section of the coating in the region in the thickness direction to its total cross-sectional area. That is to say, the cross-sectional porosity of the aramid coating refers to the ratio of the area of all pores in the cross section of the entire aramid coating along the thickness direction to its cross-sectional area; the cross-sectional porosity located in the 1 / 2 thickness area of the aramid coating surface refers to the ratio of the area of all pores in the cross section of the 1 / 2 thickness area of the aramid coating surface (away from the base film) in the thickness direction to the cross-sectional area of the 1 / 2 thickness area; the cross-sectional porosity located in the inner 1 / 2 thickness area of the aramid coating refers to the ratio of the area of all pores in the cross section of the 1 / 2 thickness area of the aramid coating inside (close to the base film) in the thickness direction to the cross-sectional area of the 1 / 2 thickness area.
[0017] The cross-sectional pore area and cross-sectional porosity can be obtained by:
[0018] The aramid coated diaphragm sample was cut along the thickness direction, and the microporous structure of the aramid coating cross section was observed under an electron microscope. Part or all of the 1 / 2 thickness area to be tested was selected (ensuring that there are more than 100 cross-sectional holes in the selected area), and all cross-sectional holes in the selected area were marked. The area of each cross-sectional hole was calculated using image J software (the scanning electron microscope image was inserted into the software, the trajectory of the micropores was drawn, and then the internal area of the trajectory was obtained).
[0019] The ratio of the sum of the areas of each cross-sectional hole to the cross-sectional area of the selected region is the cross-sectional porosity of the corresponding region.
[0020] Furthermore, the increased value of air permeability per unit thickness of the aramid coating of the aramid coated diaphragm of the present invention is 20-35s / 100cc / μm, for example, 20, 23, 26, 29, 32, 35s / 100cc / μm.
[0021] The increase in air permeability per unit thickness of the aramid coating = (air permeability of the aramid coated diaphragm after coating - air permeability of the base membrane) / coating thickness.
[0022] Furthermore, the ionic conductivity of the aramid coated diaphragm of the present invention is 1.5-2.2 mS / cm.
[0023] Furthermore, the aramid coated diaphragm of the present invention has a liquid absorption rate of 100-160% and a liquid retention rate of 70-140%.
[0024] Furthermore, the heat shrinkage rate of the aramid coated diaphragm of the present invention in the machine direction MD and the transverse direction TD after being kept at 130°C for 1 hour is less than 3%; preferably, the heat shrinkage rate of the aramid coated diaphragm in the machine direction MD after being kept at 130°C for 1 hour is less than 1.8%, and the heat shrinkage rate in the transverse direction TD is less than 1.5%.
[0025] Furthermore, the nickel-rich positive electrode|graphite negative electrode lithium ion battery assembled with the aramid coated diaphragm of the present invention, combined with a chelating agent (such as EDTA, DPPE, etc.) in the electrolyte, has a discharge capacity retention rate of >95% (up to 96.9%) and a coulombic efficiency of >98% (up to 99.6%) after 300 cycles.
[0026] The base film may be any base film suitable for lithium batteries known in the prior art, for example, it may be a microporous film, a porous film or a non-woven film, and may be a single base film or a composite base film, such as a polyethylene microporous film, a polypropylene microporous film, a polyethylene / polypropylene / polyethylene three-layer composite microporous film, a polyvinylidene fluoride microporous film, a polyimide microporous film, a non-woven fabric, etc., but not limited thereto. The source of the base film is not limited, and it may be commercially available or prepared by itself according to existing methods. For example, a polyolefin base film may be prepared by uniaxial or biaxial stretching using a wet or dry process, or by a thermally induced phase separation method.
[0027] There is no particular restriction on the thickness of the base film. Generally speaking, the thickness is less than 20 μm, for example, 4-20 μm, such as 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 μm.
[0028] There is no particular limitation on the pore size and porosity of the base membrane as long as it is suitable for use as a separator for a lithium battery. For example, the porosity can be 40-55%, for example 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%.
[0029] There is no particular limitation on the air permeability of the base film as long as it is suitable for use as a separator for a lithium battery. For example, the air permeability may be 50-500 s / 100 cc, such as 50, 60, 80, 100, 150, 200, 300, 400, 500 s / 100 cc.
[0030] The main components of the aramid coating are aramid (aramid fiber) and inorganic filler.
[0031] There is no particular limitation on the thickness of the aramid coating as long as it is suitable for use as a separator for a lithium battery, for example, it may be 1-4 μm, such as 1, 2, 3, or 4 μm.
[0032] There is no particular limitation on the type of aramid. In one embodiment, the aramid is selected from at least one of poly(m-phenylene isophthalamide) and poly(p-phenylene terephthalamide).
[0033] There is no particular restriction on the inorganic filler. In one embodiment, the inorganic filler is selected from at least one of a ceramic material, a nanowire material or a nanotube material; wherein the ceramic material can be selected from one or more of Al2O3, SiO2, TiO2, ZrO2, BaSO4, BaTiO3, MgO, CaO, AlOOH, and SiC; the nanowire material can be selected from one or more of carbon nanowires, attapulgite, nanosilver wire, boron carbide nanowire, nanocellulose, copper hydroxide nanowire, silicon monoxide nanowire, and hydroxyapatite nanowire; the nanotube material can be selected from one or more of carbon nanotubes, nanosilver tubes, boron carbide nanotubes, copper hydroxide nanotubes, silicon monoxide nanotubes, and hydroxyapatite nanotubes. The average particle size of the ceramic material is 0.1 to 0.5 μm, and the aspect ratio of the nanowire material or the nanotube material is 500-3000.
[0034] In one embodiment, the inorganic filler is an inorganic filler having active groups on the surface; the active groups are capable of adsorbing transition metal ions, and the active groups include at least one of amino, imino, carboxyl, hydroxyl, and thiol.
[0035] The separator of the present invention including the aramid coating layer having non-uniform pore sizes in the thickness direction thereof may be manufactured according to the following method, but the present invention is not limited thereto.
[0036] A second aspect of the present invention provides a method for preparing the above-mentioned aramid coated diaphragm, comprising the following steps:
[0037] (1) mixing an aramid stock solution, inorganic particles and an optional organic solvent, and dispersing the mixture in a high-speed disperser and a high-pressure homogenizer to obtain an aramid coating slurry;
[0038] The aramid stock solution comprises aramid (poly(m-phenylene isophthalamide) or poly(p-phenylene terephthalamide), a cosolvent and an organic solvent, wherein the cosolvent is one or more of CaCl2, KOH, LiCl, LiBr or pyridine, and the organic solvent is one of N-methylpyrrolidone (NMP) and dimethylacetamide (DMAc);
[0039] The aramid stock solution has an aramid solid content of 1.5-4wt% and a co-solvent content of 6-10%; the rotational viscosity of the aramid stock solution is 12000-16000 mPa·s;
[0040] The solid content of the aramid coating slurry (total mass of aramid and inorganic particles / total mass of inorganic particles, aramid stock solution and optional organic solvent) is 3% to 15%;
[0041] (2) coating the aramid coating slurry on at least one side of the base film, steam bathing, washing with water, and drying to obtain an aramid coated diaphragm;
[0042] The steam bath temperature is 45-70°C and the steam bath relative humidity is RH 50-95%.
[0043] The concentration of the cosolvent and the aramid solid content in the aramid stock solution will increase the viscosity, reduce the phase separation rate at the interface, and easily form a thicker skin layer. The skin layer increases the exchange resistance between the solvent and the non-solvent inside the coating, delays the phase separation inside the coating, and inhibits the macropores in the coating. In addition, when the viscosity is high, the thermodynamic stability decreases, the phase separation rate at the interface is accelerated, and the instantaneous phase separation is easy to form macropores.
[0044] The cosolvent has the functions of promoting the dissolution of aramid, increasing the viscosity of the aramid stock solution and forming pores. As the concentration of the cosolvent increases, the dissolution of aramid is promoted, the thermodynamic stability of the slurry system is improved, and the phase separation rate is reduced, that is, it tends to delay the phase separation, resulting in the formation of a skin layer on the surface. In addition, the increase in viscosity further aggravates the formation of the skin layer, which ultimately leads to the inhibition of the macroporous structure inside the coating. When the concentration of the cosolvent continues to increase, its pore-forming effect is obvious after washing with water, the skin layer on the surface of the coating is not obvious, and the pore structure within the cross-section of the coating is relatively rich.
[0045] Lowering the steam bath temperature, reducing the mass transfer rate between the solvent and non-solvent water in the slurry, and delaying phase separation are beneficial to the inhibition of macropores in the coating.
[0046] Step (1):
[0047] Preferably, the mass ratio of aramid to inorganic particles is 1-2:3;
[0048] Preferably, the high-speed dispersion speed is 3000-10000rpm, and the high-speed dispersion time is 1-2h;
[0049] Preferably, the dispersion pressure of the high-pressure homogenizer is 300-1000 bar.
[0050] Step (2):
[0051] There is no particular limitation on the coating method in step (2), as long as it is suitable for preparing the diaphragm, such as wire rod coating, micro gravure roller coating, doctor blade coating, narrow slot extrusion coating, etc.
[0052] There is no special limitation on the water washing method. Generally, 2-8 levels of water tanks are set, all of which are pure water settings. The pure water in the water tank adopts an overflow method from back to front. Each water tank outlet needs to be equipped with an air knife or pressure roller to reduce the diaphragm from carrying water from the previous water tank into the next water tank.
[0053] There is no particular limitation on the drying method as long as it is suitable for preparing the separator. For example, drying may be used, preferably at 60-90°C.
[0054] According to a third aspect of the present invention, there is provided an electrochemical device comprising the above-mentioned aramid coated diaphragm.
[0055] Aramid coated diaphragms can be used in different types of electrochemical devices, such as various types of batteries, which can be selected according to actual needs. For example, they can be used in secondary batteries such as lithium ion batteries and sodium ion batteries.
[0056] Beneficial effects:
[0057] The present invention differentiates the cross-sectional pore size of the coating layer. On the one hand, the low pore size characteristics of the surface coating (away from the base film side) can enhance the adsorption and blocking effect of the active functional groups on the surface of the coating film on transition metal ions, thereby improving the capacity retention rate and coulomb efficiency of the lithium-ion battery. On the other hand, the higher pore size of the inner coating (close to the base film side) can effectively ensure the coating film has good liquid absorption and retention, thermal shrinkage, ionic conductivity and other properties, allowing the lithium-ion battery to achieve high-rate charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 A cross-sectional view of an aramid-coated diaphragm of the present invention and a schematic diagram of an aramid coating having a non-uniform pore size structure in the thickness direction are shown;
[0059] Illustration: 1-base film; 2-aramid coating; 3-aramid; 4-inorganic filler; 21-1 / 2 thickness area on the surface of aramid coating; 22-1 / 2 thickness area inside aramid coating;
[0060] Figure 2 This is a cross-sectional electron microscope image of the coated diaphragm obtained in Example 1;
[0061] Figure 3 This is a cross-sectional electron microscope image of the coated diaphragm obtained in Comparative Example 1;
[0062] Figure 4 This is a cross-sectional electron micrograph of the coated diaphragm obtained in Comparative Example 2;
[0063] Figure 5 This is a cross-sectional electron microscope image of the coated diaphragm obtained in Comparative Example 3. DETAILED DESCRIPTION
[0064] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0066] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0067] Example 1
[0068] Take 3.2g Al2O3 with an average particle size of 100nm and 80g para-aramid stock solution with a solid content of 2% (the solvent is NMP, the co-solvent CaCl2 accounts for 6%, and the rotational viscosity is 12500mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used, and then the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated during the homogenization and dispersion process to cool down, and a slurry with a solid content of about 5.77% is obtained.
[0069] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod to obtain a coated wet film, which was then subjected to a steam bath (50°C, humidity RH 85%), water washing, and drying (60°C, 30 min) to obtain a coated dry film with a coating thickness of approximately 3 μm.
[0070] Prepare cross-sectional samples of the coated film: fold the aluminum foil in half, and then clamp the cut diaphragm sample in the aluminum foil close to the fold line of the aluminum foil. At this time, make the diaphragm about 3mm shorter than the aluminum foil at one end. Apply a proper amount of glue in this blank space, and then quickly close the aluminum foil. Cut off the excess aluminum foil with a blade, and then glue the sample to the silicon plate. Use a blade to cut the diaphragm vertically along the edge of the silicon plate to obtain the cross section of the sample to be processed. Paste the above cross-sectional sample on a special sample stage, and the silicon plate protrudes from the edge of the sample stage by about 2mm. Install the special sample stage on the cross-sectional processing sample holder, press the sample stage fixing screw with a hexagonal rod to slide it next to the MASK (baffle), and place the sample close to the MASK, and then tighten the fixing screw. Turn on the IM4000plus ion milling instrument for grinding.
[0071] The cross-sectional electron microscopy images obtained are shown in Figure 2 shown.
[0072] Example 2
[0073] Take 4.8g Al2O3 with an average particle size of 100nm and 80g para-aramid stock solution with a solid content of 3% (the solvent is NMP, the co-solvent CaCl2 accounts for 8%, and the rotational viscosity is 13600mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used, and then the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated during the homogenization and dispersion process to cool down, and a slurry with a solid content of about 8.49% is obtained.
[0074] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod to obtain a coated wet film, which was then subjected to a steam bath (60°C, humidity RH 85%), water washing, and drying (60°C, 30 min) to obtain a coated dry film with a coating thickness of approximately 3 μm.
[0075] Example 3
[0076] Take 6.4g Al2O3 with an average particle size of 100nm and 80g para-aramid stock solution with a solid content of 4% (the solvent is NMP, the co-solvent CaCl2 accounts for 10%, and the rotational viscosity is 15400mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used, and then the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated during the homogenization and dispersion process to cool down, and a slurry with a solid content of about 11.11% is obtained.
[0077] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod to obtain a coated wet film, which was then subjected to a steam bath (70°C, humidity RH 85%), water washing, and drying (60°C, 30 min) to obtain a coated dry film with a coating thickness of approximately 3 μm.
[0078] Comparative Example 1
[0079] Take 2g of Al2O3 with an average particle size of 100nm and 80g of para-aramid stock solution with a solid content of 5% (the solvent is NMP, the co-solvent CaCl2 accounts for 12%, and the rotational viscosity is 18500mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used. Then, the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated during the homogenization and dispersion process to cool down, and a slurry with a solid content of about 7.32% is obtained.
[0080] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod, and the resulting wet coating was subjected to a coagulation bath (water: NMP = 70:30), water washing, and drying (60°C, 30 min) to obtain a coating dry film with a coating thickness of approximately 3 μm.
[0081] The cross-sectional electron microscopy image of the obtained coated diaphragm is shown in Figure 3 shown.
[0082] Comparative Example 2
[0083] Take 8.0g Al2O3 with an average particle size of 100nm and 80g para-aramid stock solution with a solid content of 5% (the solvent is NMP, the co-solvent CaCl2 accounts for 16%, and the rotational viscosity is 20500mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used, and then the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated to cool the mixture during the homogenization and dispersion process to obtain a slurry with a solid content of about 13.64%.
[0084] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod, and the resulting wet coating was subjected to a coagulation bath (water: NMP = 70:30), water washing, and drying (60°C, 30 min) to obtain a coating dry film with a coating thickness of approximately 3 μm.
[0085] The cross-sectional electron microscopy image of the obtained coated diaphragm is shown in Figure 4 shown.
[0086] Comparative Example 3
[0087] Take 2.4g Al2O3 with an average particle size of 100nm and 80g para-aramid stock solution with a solid content of 2% (the solvent is NMP, the co-solvent CaCl2 accounts for 6%, and the rotational viscosity is 8920mPa·s), and disperse them at a high speed of 8000rpm for 1h. During the high-speed dispersion, an ice bath is used. Then, the mixture is dispersed once at a pressure of 500bar by a high-pressure homogenizer. Condensed water is circulated during the homogenization and dispersion process to cool down, and a slurry with a solid content of about 4.85% is obtained.
[0088] A 7 μm PE-based membrane (produced by China National Materials Lithium Membrane Co., Ltd., with a porosity of 34% and an air permeability of 135 s / 100 cc) was coated with a wire rod to obtain a coated wet film, which was then subjected to a steam bath (30°C, humidity RH 85%), water washing, and drying (60°C, 30 min) to obtain a coated dry film with a coating thickness of approximately 3 μm.
[0089] The cross-sectional electron microscopy image of the obtained coated diaphragm is shown in Figure 5 shown.
[0090] Test Case
[0091] The coated diaphragms of the embodiment and the comparative example were respectively subjected to the following tests:
[0092] [Cross-sectional porosity] The area of the cross-sectional holes at 1 / 2 thickness on the surface and 1 / 2 thickness inside is measured according to the above method, and the cross-sectional porosity of the corresponding area is obtained based on the ratio of the total area of the cross-sectional holes to the cross-sectional area of the area.
[0093] [Thickness] Tested according to the method specified in GB / T6672-2001;
[0094] [Air permeability] Tested according to the method specified in GB / T 1038;
[0095] [Ionic conductivity] The test equipment for ionic conductivity is an electrochemical workstation, and the method used is the AC impedance method. The ionic conductivity σ = d / Rb × S, where d is the thickness of the diaphragm, Rb is the internal resistance of the diaphragm in the simulated battery, and S is the test diaphragm area.
[0096] [Liquid absorption and retention rate] The diaphragm is weighed on an electronic balance, and the initial weight is recorded as W1. It is then placed in a beaker containing electrolyte, completely immersed in the sealed beaker, and soaked for 60 minutes. The soaked sample is taken out and weighed, which is recorded as W2. The weighed sample is left to stand in a fume hood for 60 minutes, and weighed, which is recorded as W3. Liquid absorption rate = (W2-W1) / W1×100%; liquid retention rate = (W3-W1) / W1×100%.
[0097] [Heat shrinkage rate] Tested in accordance with the requirements of GB / T36363-2018. Take a 100*100mm sample from the coating film, put it in a blast oven at 130℃ for 1h, and the heat shrinkage rate can be calculated by the following formula:
[0098] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;
[0099] TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) ÷ TD length before heating × 100;
[0100] [Discharge capacity retention rate, coulombic efficiency] The capacity retention rate of a battery cell measures the ability of the battery cell to maintain capacity during the charge and discharge cycle, that is, the ability to resist capacity decay. Its value is defined as the ratio of the fully discharged capacity to the initial capacity of the battery cell (the positive electrode is a nickel-rich positive electrode, the negative electrode is graphite, the electrolyte is 1M LiPF6, EC:EMC=3:7, containing EDTA) after the 300th cycle, where the state of charge (SOC) is 100% when not discharged and 0% SOC after full discharge. Coulombic efficiency is calculated as the ratio of the discharge capacity to the charge capacity in the same cycle.
[0101] The results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aramid coated diaphragm, characterized in that: The aramid coated diaphragm comprises: Basement membrane, and An aramid coating containing aramid and an inorganic filler coated on at least one side of the base film, wherein the inorganic filler is filled in a fiber network structure formed by the aramid; The cross-sectional porosity of the aramid coating is 28.5-46%, and the aramid coating shows inconsistent pore sizes in the thickness direction, wherein the ratio of the cross-sectional porosity in the 1 / 2 thickness area on the surface of the aramid coating to the cross-sectional porosity in the 1 / 2 thickness area inside the aramid coating is <1.
2. The aramid coated diaphragm according to claim 1, characterized in that: The cross-sectional porosity at the 1 / 2 thickness region of the aramid coating surface is 25.4-43.6%, preferably 36.0-41.0%; The cross-sectional porosity of the 1 / 2 thickness region inside the aramid coating is 31.6-45.4%, preferably 39.0-44.0%.
3. The aramid coated diaphragm according to claim 1, characterized in that: The nickel-rich positive electrode|graphite negative electrode lithium ion battery assembled with the aramid coated diaphragm is combined with a chelating agent in the electrolyte. After 300 cycles, the discharge capacity retention rate is greater than 95%, and the coulomb efficiency is greater than 98%.
4. The aramid coated diaphragm according to claim 1, characterized in that: The aramid coated diaphragm has an aramid coating permeability increase per unit thickness of 20-35s / 100cc / μm.
5. The aramid coated diaphragm according to claim 1, characterized in that: The ionic conductivity of the aramid coated diaphragm is 1.5-2.2 mS / cm.
6. The aramid coated diaphragm according to claim 1, characterized in that: The aramid coated diaphragm has a liquid absorption rate of 100-160% and a liquid retention rate of 70-140%.
7. The aramid coated diaphragm according to claim 1, characterized in that: The heat shrinkage of the aramid coated diaphragm in the machine direction MD and the transverse direction TD after being kept at 130°C for 1 hour is less than 3%; preferably, the heat shrinkage of the aramid coated diaphragm in the machine direction MD after being kept at 130°C for 1 hour is less than 1.8%, and the heat shrinkage of the transverse direction TD is less than 1.5%.
8. A method for preparing an aramid coated diaphragm, characterized in that: The following steps are involved: (1) mixing an aramid stock solution, inorganic particles and an optional first organic solvent, and dispersing the mixture in a high-speed disperser and a high-pressure homogenizer to obtain an aramid coating slurry; The aramid stock solution comprises aramid, a cosolvent and a second organic solvent, wherein the cosolvent is one or more of CaCl2, KOH, LiCl, LiBr or pyridine, and the second organic solvent is one of N-methylpyrrolidone and dimethylacetamide; The aramid stock solution has an aramid solid content of 1.5-4wt%, and a co-solvent content of 6-10%; the rotational viscosity of the aramid stock solution is 12000-16000 mPa·s; and the solid content of the aramid coating slurry is 3% to 15%; (2) coating the aramid coating slurry on at least one side of the base film, steam bathing, washing with water, and drying to obtain an aramid coated diaphragm; The steam bath temperature is 45-70°C and the steam bath relative humidity is RH 50-95%.
9. The preparation method according to claim 6, characterized in that: In step (1), the mass ratio of aramid to inorganic particles is 1-2:3; the high-speed dispersion speed is 3000-10000 rpm, and the high-speed dispersion time is 1-2 hours; and the dispersion pressure of the high-pressure homogenizer is 300-1000 bar.
10. An electrochemical device, characterized in that: The electrochemical device comprises the aramid coated diaphragm according to any one of claims 1-7.
Citation Information
Cited By
Diaphragm and preparation method and application thereof
CN120511432A
A diaphragm and a method for manufacturing and using the same
CN120511432B
Composite diaphragm, preparation method thereof and lithium ion battery
CN121709864A